Peran Perempuan dalam Penology dan Kekerasan Seksual pada Anak: Sebuah Studi Literatur - Giya Dwi Ilham; Olvin Kristin Banamtuan; Isty Rahmania (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
This study investigates the role of women in the field of penology and the impact of sexual violence on children through literature analysis. The main focus is to provide women's contribution in handling crime and rehabilitation in prison institutions as well as implementing policies for the safety and welfare of children who are victims of sexual violence. Through in-depth literature observations, this research provides insight into the various perspectives and approaches used in addressing these issues.